Stimulus Kredit Perbankan: Kebijakan Penanggulangan Risiko Kredit Akibat Coronavirus Disease 2019 (COVID-19) di Indonesia - Hari Sutra Disemadi (University of Udayana, 2021)
The spread “of Coronavirus Disease 2019 or COVID-19 affects the economic stability of a country. Indonesia is one of the countries whose economic stability is disrupted “due to the spread of COVID-19. The problem currently facing Indonesia is that the performance and capacity of debtors in carrying out their credit obligations has been disrupted by the spread of COVID-19, which has the potential to disrupt banking performance in credit management. Therefore, the aim of this research is to find out and study the government's efforts in encouraging the banking intermediation function, maintaining financial system stability and supporting economic growth, a policy is needed as a legal strategy in overcoming the impact of the COVID-19 pandemic, particularly the impact on the performance and capacity of debtors in carry out its credit obligations. The research method used is a normative legal research method by utilizing legal materials. The results of this study indicate that the regulation of credit risk management policies” in Indonesia has been regulated in existing laws and regulations such as the Law on Banking; Law concerning Sharia Banking; Bank Indonesia Regulations; and Financial Services Authority Regulations. “The effort chosen by the government in overcoming economic instability due to the spread of COVID-19 is the issuance of a policy to provide a national economic stimulus through the application of Financial Services Authority Regulation No. 11/POJK.03/2020. This policy is “countercyclical” due to the” policies used in maintaining the stability of the economic” cycle. Penyebaran Coronavirus Disease “2019 atau COVID-19 mempengaruhi kestabilan ekonomi suatu negara. Indonesia merupakan salah satu negara yang kestabilan ekonominya terganggu akibat penyebaran COVID-19. Permasalahan yang dihadapi Indonesia saat ini adalah kinerja serta kapasitas debitur dalam melaksanakan kewajiban kreditnya telah terganggu dengan adanya penyebaran COVID-19, sehingga berpotensi mengganggu kinerja perbankan dalam pengelolaan kredit. Maka dari itu, tujuan penelitian ini adalah untuk mengetahui dan mengkaji upaya pemerintah dalam mendorong fungsi intermediasi perbankan, menjaga stabilitas sistem keuangan dan mendukung pertumbuhan ekonomi diperlukan adanya” kebijakan sebagai strategi hukum dalam menanggulangi dampak Pandemi COVID-19, “khususnya dampak bagi kinerja serta kapasitas debitur dalam “melaksanakan kewajiban kreditnya. Metode penelitian yang digunakan adalah metode penelitian hukum normatif dengan memanfaatkan bahan-bahan hukum. Hasil penelitian ini menunjukkan pengaturan kebijakan manajemen risiko kredit di Indonesia telah diatur dalam peraturan perundang-undangan yang ada seperti Undang-Undang tentang Perbankan; Undang-Undang tentang Perbankan Syariah; Peraturan Bank Indonesia; dan Peraturan Otoritas Jasa Keuangan. Upaya yang dipilih oleh pemerintah dalam mengatasi ketidakstabilan perekonomian akibat penyebaran COVID-19 adalah diterbitkannya kebijakan pemberian stimulus perekonomian nasional melalui penerapan Peraturan Otoritas Jasa Keuangan No. 11/POJK.03/2020.” Kebijakan ini bersifat “countercyclical” dikarenakan kebijakan” yang digunakan dalam menjaga kestabilan siklus perekonomian